2023
DOI: 10.1108/ecam-08-2022-0780
|View full text |Cite
|
Sign up to set email alerts
|

Transforming construction health and safety management during COVID-19 pandemic using innovative technologies: PLS-SEM approach

Abstract: PurposeThis study aims to investigate technology-based health and safety (H&S) management to control the spread of disease on construction sites using a partial least squares structural equation modelling (PLS-SEM) approach.Design/methodology/approachAn extensive literature review is conducted to develop a conceptual framework. The variables identified from the literature review are included in a cross-sectional survey which gathered a total of 203 valid feedback. The variables for challenges are grouped u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…These results showed that all measurement items should not belong to a single factor. In addition, the CMB issue was scouted out by evaluating the variance inflation factors (VIFs) of the latent variables in the model (Kum et al. , 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results showed that all measurement items should not belong to a single factor. In addition, the CMB issue was scouted out by evaluating the variance inflation factors (VIFs) of the latent variables in the model (Kum et al. , 2023).…”
Section: Methodsmentioning
confidence: 99%
“…These results showed that all measurement items should not belong to a single factor. In addition, the CMB issue was scouted out by evaluating the variance inflation factors (VIFs) of the latent variables in the model (Kum et al, 2023). highlight that the VIF collinearity method is well-suited to ascertain the CMB issue in a partial least squares structural equations modeling (PLS-SEM) model.…”
Section: Common Methods Bias and Nonresponse Biasmentioning
confidence: 99%
“…The advantages of IBM SPSS include an intuitive interface, the ability to process large datasets, and support for various types of statistical analysis. In the context of international business expansion, the use of IBM SPSS can help companies identify new market opportunities, analyze risk factors, and formulate effective expansion strategies [21].…”
Section: Use Of Ibm Spss In Business Researchmentioning
confidence: 99%
“…, 2022). Other varied studies have been conducted in areas including health and safety management (Kum et al. , 2023; Sadeh et al.…”
Section: Introductionmentioning
confidence: 99%
“…Academia, in partnership with the industry, has reported on the impact of COVID-19 on the construction industry from various perspectives, such as the general construction industry (Ogunnusi et al, 2020), the health and safety of the construction workforce (Pamidimukkala et al, 2021), and the use and adoption of digital technologies . Other varied studies have been conducted in areas including health and safety management (Kum et al, 2023;Sadeh et al, 2023), construction performance (Gumusburun Ayalp and Civici, 2023), and construction supply chain management (Sutterby et al, 2023). Considering the challenges, how the pandemic and the associated mitigation measures have affected QA is still unclear.…”
mentioning
confidence: 99%